PENGARUH LIKUIDITAS DAN PERSISTENSI LABA TERHADAP KUALITAS LABA DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Dewi Kusuma Wardani; Vera Anggrenita (Bajang Institute, 2022)
This study aims to examine the effect of liquidity and earnings persistence on earnings quality with firm size as a moderating variable. The sample used in this study is a manufacturing company. Sampling using purposive sampling method using annual financial statements. Data analysis using SPSS 21. This research technique uses multiple linear analysis and sub-group analysis. The results showed that liquidity had no effect on earnings quality. Earnings persistence has a negative effect on earnings quality. Firm size can moderate the effect of earnings persistence on earnings quality. Firm size cannot moderate the effect of liquidity on earnings quality.